Discordance of HIV and HSV-2 biomarkers and self-reported sexual behaviour among orphan adolescents in Western Kenya. (6th November 2014) - Cho, Hyunsan; Luseno, Winnie; Halpern, Carolyn; Zhang, Lei; Mbai, Isabella; Milimo, Benson; Hallfors, Denise Dion
Abstract : Background: This paper examines the discordance between biological data of HIV and herpes simplex virus type 2 (HSV-2) infections and self-reported questionnaire responses among orphan adolescents in Western Kenya. Methods: In 2011, 837 orphan adolescents from 26 primary schools were enrolled in an HIV prevention trial. At baseline, blood samples were drawn for HIV and HSV-2 infection biomarker testing, and participants completed an audio computer-assisted self-interviewing survey. Results: Comparing biological data with self-reported responses indicated that 70% of HIV-positive (7 out of 10) and 64% of HSV-2-positive (18 out of 28 positive) participants reported never having had sex. Among ever-married adolescents, 65% (57 out of 88) reported never having had sex. Overall, 10% of study participants appeared to have inconsistently reported their sexual behaviour. Logistic regression analyses indicated that lower educational level and exam scores were significant predictors of inconsistent reporting. Conclusions: Our study demonstrates the discordance between infections measured by biomarkers and self-reports of having had sex among orphan adolescents in Kenya. In order to detect programme effects accurately in prevention research, it is necessary to collect both baseline and endline biological data. Furthermore, it is recommended to triangulate multiple data sources about adolescent participants' self-reported information about marriage and pregnancies from school records and parent/guardians to verify the information. Researchers should recognise potential threats to validity in data and design surveys to consider cognitive factors and/or cultural context to obtain more accurate and reliable information from adolescents regarding HIV/sexually transmitted infection risk behaviours. Clinical Trail Registration number: NCT01501864.